2014
DOI: 10.1002/hpm.2249
|View full text |Cite
|
Sign up to set email alerts
|

Coordination pays off: a comparison of two models for organizing hip fracture care, outcomes and costs

Abstract: SUMMARYBackground and purpose With the "graying" of the population, hip fractures place an increasing burden on health systems and call for efficient forms of care. The aim was to compare two models of organizing hip fracture care at one university hospital working at two sites. The differences in organization were coordinated care provided in one of the sites and traditional care, divided between different institutions, in the other. Material and methods The study was conducted at a Swedish university hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Similar factors may explain observed changes in the disposition at discharge between the 2 periods. 10,14,20 Alternatively, the significant increase in discharge to SNFs appreciated during 2008-10 may be indicative of harmonized efforts on the part of hospitals and healthcare providers to streamline the surgical treatment and rehabilitation of patients with femoral neck fractures. Similar findings have been appreciated in other works evaluating coordinated care for patients with hip fractures.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar factors may explain observed changes in the disposition at discharge between the 2 periods. 10,14,20 Alternatively, the significant increase in discharge to SNFs appreciated during 2008-10 may be indicative of harmonized efforts on the part of hospitals and healthcare providers to streamline the surgical treatment and rehabilitation of patients with femoral neck fractures. Similar findings have been appreciated in other works evaluating coordinated care for patients with hip fractures.…”
Section: Discussionmentioning
confidence: 95%
“…Similar findings have been appreciated in other works evaluating coordinated care for patients with hip fractures. 14 The odds of FTR and complications were the only quality measures significantly different in the period after health reform. Observed reductions in FTR are indicative of improved quality in hospital care to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 37 included studies, only ten studies were RCTs [16][17][18][19][20][21][22][23][24][25]. Six studies were prospective cohort studies [26][27][28][29][30][31], ten were prospective cohort studies with a retrospective control [32][33][34][35][36][37][38][39][40][41], ten were retrospective cohort studies [42][43][44][45][46][47][48][49][50][51], and one study was a prospective pre-and post-intervention study [52]. Results of the Cochrane collaboration's tool for assessing risk of bias are given in Table 2.…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
“…All studies except Shyu 2008 et al [18] that reported data on 1-year mortality could be included in a meta-analysis [27,31,32,35,38,39,41,42,44,[47][48][49][50] (Fig. 5).…”
Section: -Year Mortalitymentioning
confidence: 99%